Tel arbre, tel fruit: the Tristan as 'tragodía' - Patrick Michael Thomas (Acta Neophilologica, 1999)
It would seem that at the very core of tragedy one finds the fatal twins of death and resurrection. We suggest that any definition of tragedy that does not take this 'sine qua non' into account is missing the mark. And that includes Aristotle's definition which, like others after him, tends to describe the outer trappings of tragedy, although the purgation of pity and fear implies a type of metaphorical death out of which the spectator arises anew.The concerns, albeit legitimate, with 'peripetia', 'anagnorisis', and 'hamartia' really do not go to the heart of the matter, it seems to us.